Evaluation of team-doctor actions during football games in Japanese professional football - Takahashi, M.; Fukuoka, S.; Nagano, A. (Journal of Science and Medicine in Sport, 2009)
There have been many studies on football (soccer) match injuries both in national leagues and international tournaments, including the World Cup. However, no previous study on the number and types of actions taken by a team-doctor during a football season has been investigated. The aim of this study is to investigate what actions and how much a team doctor acts during professional football matches in a typical season of the Japanese professional football league (J-League). Injuries were prospectively recorded by team doctors with a Japanese professional league club during the 2004 season. Data recorded by the attending doctor after each match included information relating to the injury, time of occurrence and actions taken by the doctor in response to the injuries. The activity of the doctor was graded into 6 categories (grade A to F). During the 42 official matches held throughout the 2004 season, a total of 67 doctor-actions were taken. The overall doctor-action frequency rate (DAFR) was 1.6 actions per match. This study demonstrated how the team doctor acts during an average football match, and provides some useful information for team-doctors who attend football matches.